A CONTRASTIVE ANALYSIS BETWEEN BAHASA INDONESIA AND ENGLISH IN KATE CHOPIN’S A STORY OF AN HOUR - Galuh Dwi Ajeng (English Department, STKIP PGRI Bandar Lampung, 2020)
Communication is not just that one person is speaking and the other is listening. In doing its duty as a means of communication, the language in each country has different characteristics. The use of language here is to show the identity of each country. In education area, learning a language as second language sometimes creates a problem. The problem deals with the difficulties in learning second language and some error that is done by learners in learning second language. Hence, this study is aimed to find the differences and the similarity between Bahasa Indonesia and English through a short story titled “A Story of an Hour” by Kate Chopin translated by Desi Ilham Sianturi. To deal with the purpose of this study the writer uses contrastive analysis method.